2019
DOI: 10.1007/s12178-019-09555-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of High Energy Distal Radius Injuries

Abstract: Purpose of Review High energy distal radius are commonly multi-fragmentary with significant comminution and/or bone loss. They can also be associated with ligamentous and soft tissue injury and neurovascular compromise. As such, reconstruction of these injuries can be challenging. This paper will review the relevant anatomy, different methods of fixation, and present techniques for difficult fractures. Recent Findings Volar locked plating is a successful, very common method of treatment for distal radius fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…VLP method has numerous functional and structural advantages, including its anatomically shaped design, early mobilization, and well-preserved wrist function. Several reports show that the VLP is related to tendon related complications, even necessitating plate removal and resurgery [8].However, we did not experience such complications in our patient group, possibly as a result of appropriate patient selection, careful soft tissue dissection and precise screw lengths. Farhan et al reported in their series of patients with AO23C3 distal radius fractures that 16% of the patients required plate removal [23].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…VLP method has numerous functional and structural advantages, including its anatomically shaped design, early mobilization, and well-preserved wrist function. Several reports show that the VLP is related to tendon related complications, even necessitating plate removal and resurgery [8].However, we did not experience such complications in our patient group, possibly as a result of appropriate patient selection, careful soft tissue dissection and precise screw lengths. Farhan et al reported in their series of patients with AO23C3 distal radius fractures that 16% of the patients required plate removal [23].…”
Section: Discussionmentioning
confidence: 58%
“…Yu et al reported a 34.5% and 28.2% complication rate in their patients treated with EF and VLP, respectively [13]. The most common complications for surgical management of distal radius fractures include loss of reduction, infection, joint stiffness due to nerve injury, tendon rupture, osteoarthritis, and tendonitis [8,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Although most DRF management strategies involve nonoperative methods, a significant trend toward surgical treatment has been noted, 5,6) largely explained by the introduction of volar locking plate (VLP) fixation, which is associated with advantages such as stable fixation, short immobilization period, and few complications. [7][8][9] In open DRFs, there is no consensus regarding operative treatment modalities, and the effectiveness of surgical fixation and its timing have been controversial and are based on the surgeon's preference. 10,11) Infection after open DRFs is a primary concern for determining the appropriate treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Смещение отломков кости при недостаточно адекватной репозиции, стойкий отек, повреждение мышц и тендинит сухожилия сгибателей пальцев могут стать причиной повреждения нервов (прежде всего, срединного) с развитием характерной симптоматики -нарушения чувствительности, невропатической боли, синдрома запястного канала, КРБС. По литературным данным, такие осложнения отмечаются в 2-8% случаев после перелома ЛК [45,46].…”
unclassified